External to internal search: Associating searching on search engines with searching on sites. Issue 5 (September 2015) - Ortiz-Cordova, Adan; Yang, Yanwu; Jansen, Bernard J.
Highlights External search and internal search cohere searching sessions. The referral query from external search can be predictive of internal searching. There are common patterns that one can use to classify internal searchers.